Historical virus isolate collections: An invaluable resource connecting plant virology's pre‐sequencing and post‐sequencing eras. (20th November 2020) - Jones, Roger A. C.; Boonham, Neil; Adams, Ian P.; Fox, Adrian
Abstract: Many laboratories maintain historical collections of preserved plant virus isolates that store a wealth of untapped data, including original type isolates, studied in the pre‐sequencing era. Currently, many recently recognized virus species exist with no supporting reference sequences. Also, many virus sequences appear new when compared to available sequences, but, on sequencing pre‐sequencing era isolates, they may coincide. Such linkages allow access to data from previously determined biological and other parameters from pre‐sequencing era studies. These linkages are increasingly being found using high‐throughput sequencing, helping clarify virus taxonomy and improving understanding of virus ecology and evolution. Thus, mistakes can be avoided in naming viruses and in combining or separating them, as well as enabling identification of unknown viruses preserved long ago. With well‐established viruses, success in dating and other evolutionary studies, and discovery of changes in regional virus populations, both depend upon comparisons between recent and old isolate sequences covering the greatest possible time periods. Such studies help reveal the extent that human activities have influenced virus evolution and changed virus populations on a global scale. Sequencing virus genomes from herbarium specimens, archaeological specimens, or living plant collections can provide complementary data. By bringing context to newly detected viruses and supporting plant pest risk analyses, linking new virus discoveries to previously generated disease symptom, host range, virus transmission, and geographical distribution data has important implications for plant health regulation. Also, historical isolates can provide an invaluable resource facilitating biosecurity investigations involving virus introductions, entry pathways, and baseline surveillance. Abstract : The benefits that sequencing plant virus isolates from historical culture collections are many, including resolving nomenclature issues, enabling dating and evolutionary studies, and improving plant health regulation.